2009
DOI: 10.1111/j.1753-4887.1998.tb01763.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chromium on Body Composition and Weight Loss

Abstract: Chromium is an essential nutrient involved in the regulation of carbohydrate and lipid metabolism. Normal dietary intake of chromium in humans and farm animals is often suboptimal. In addition to its effects on glucose, insulin, and lipid metabolism, chromium has been reported to increase lean body mass and decrease percentage body fat, which may lead to weight loss in humans. The effects of chromium on body composition are controversial but are supported by animal studies, which increase their validity. A sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(43 citation statements)
references
References 32 publications
3
39
1
Order By: Relevance
“…The fact that not all studies show beneficial effects of supplemental Cr (12,23,24) is consistent with the expected observations that not all individuals are marginally or overtly deficient in Cr. In addition to the selection of subjects, duration of study and form of Cr, the effects of Cr may be masked by poor diets and a sedentary lifestyle.…”
Section: Chromiumsupporting
confidence: 74%
“…The fact that not all studies show beneficial effects of supplemental Cr (12,23,24) is consistent with the expected observations that not all individuals are marginally or overtly deficient in Cr. In addition to the selection of subjects, duration of study and form of Cr, the effects of Cr may be masked by poor diets and a sedentary lifestyle.…”
Section: Chromiumsupporting
confidence: 74%
“…The 1000 mg dose was chosen because it has been shown to be safe and effective in modifying blood sugar and insulin levels 18,29 and used in other clinical trials. 30 Subjects randomized to chromium picolinate were instructed to ingest a 500-mg capsule twice per day during the intervention period for a total ingestion of 1000 mg per day for 6 months.…”
Section: Interventionsmentioning
confidence: 99%
“…In 2001 the Institute of Medicine and the National Academy of Sciences established Dietary Reference Intakes (DRI) for Chromium, ranging from 0.2 mg for infants to a maximum of 45 mg in lactating mothers [13] . Chromium is used in weight loss supplements due to purported effects of decreasing body fat and increasing basal metabolic rate [14,15] . A recent meta-analysis of available RCTs concluded that weight reduction with chromium although statistically significant was not clinically meaningful [2] .…”
Section: Discussionmentioning
confidence: 99%